Business Process Redesign: A Systematic Review of Evaluation Approaches - Tsakalidis, George; Vergidis, Kostas (Decision Making: Applications in Management and Engineering, 2024)
The continuous and systematic redesign of key business processes is very important for businesses and organizations that seek to achieve cost savings and efficiency enhancements. Selecting the most impactful processes and ensuring a successful redesign initiative remains an important topic that motivated the authors to conduct a Systematic Literature Review (SLR) on Business Process Redesign (BPR) Evaluation methodologies by applying an established eight-step SLR guide. The review sheds light on the current state of research and highlights the research gap by considering two dimensions of BPR artifacts: (a) the type of evaluation and (b) the generalizability of the existing approaches. The findings indicate that there is a lack of systematic methodologies in literature that properly evaluate the redesign capacity of models prior to implementation. Additionally, the existing methodologies do not cumulatively evaluate the quality characteristics that are necessary for BPR implementation or the applicability of BPR heuristics, and do not bear the generalizability to be readily used in a more general context. This paper aims to provide researchers with the necessary context and motivation to bridge this gap and further systematize BPR methodologies that can preselect the most suitable business processes for redesign.